Inspection of Internal Defects In Concrete Structures by Scanning Image Analysis - Zacoeb, Achfas (Rekayasa Sipil, 2010)
This paper describes one of visual inspection devices that developed with small borehole and to be named as Stick Scanner (SS) for internal concrete structure by using scanning technique. The advantage of SS is making the possibility for effective and secure working with a good precision to obtain plural information from one inspection mark such as crack width, crack depth, carbonation depth, corrosion etc in rapid way (about 30 minutes for one inspection mark). The use of small inspection borehole also gives a faster restoration and no significance damage effect towards the integrity of existing structures. The measurement and assessment process are conducted by analyzing of captured image in photograph stage.Â